Aplicação de catalisador core-shell à redução fotocatalítica de selênio - Fuziki, Maria Eduarda Kounaris (2019)
In the present work, the synthesis of CoFe2O4@TiO2core-shell photocatalysts was performed by the sol-gel method, followed by their characterization and application to the Se (IV) photocatalytic reduction. To guide both catalyst synthesis and photocatalytic experiments, a central composite design was applied. The considered factors were: calcination temperature, titanium isopropoxide concentration (% v/v) in ethanol used in catalyst synthesis and pH of the solution used in the photocatalytic test. The techniques applied for the photocatalysts characterization were: N2 adsorption-desorption measurement, photoacoustic spectroscopy (PAS), X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive Xray spectroscopy (EDS) and point of zero charge (PZC) determination. The results indicated that the most significant factors for photocatalytic removal of Se (IV) were the calcination temperature and the pH of the solution. The best conditions for increasing selenium removal within 2 minutes of photocatalysis are lower calcination temperatures (around 300 ºC) and pH around 3.5. The percentage of isopropoxide in ethanol used in the synthesis had little influence on both selenium photoreduction and catalyst properties. The calcination temperature also significantly affected the specific surface areas, bandgapand structure of the photocatalysts.